Economic Development and Environmental Degradation: Testing the Existence of an Environmental Kuznets Curve At Regional Level - George Halkos (European Regional Science Association (ERSA), 2006)
This paper uses a dynamic panel data for 23 OECD and 50 non-OECD countries for the time period 1960-1990 in order to estimate the relationship between economic development (in the form of GDP) and environmental pollution (in the form of sulphur emissions)
Keywords: 330